ANALYSIS OF THE USE OF CCTV IN PUNISHING TRAFFIC VIOLATORS - Vincentius Patria Setyawan (Jurnal Humaniora & Sosial Sains, 2024)
Advances in information technology have penetrated various aspects of people's lives. One aspect that has not been untouched by technological advances is the field of law enforcement. Law enforcement in the field of traffic violations currently uses CCTV to photograph or record violations committed by traffic rule violators. This research aims to determine the role of CCTV in proving cases of traffic violations, and guaranteeing and protecting privacy rights in the case of using CCTV for traffic violators. This article was written using normative legal research methods with a conceptual approach. The legal materials used in writing this article are primary legal materials and secondary legal materials. The results of this research show that CCTV footage is valid evidence to be submitted to prove a traffic violation, and does not conflict with the right to privacy.